Kaʻu Community Asthma Management Program - Luzviminda Banez Miguel (JMIR Publications, 2020)
The "Kaʻu Community Asthma Management Program" (KCAMP) is a quality improvement and evidence-based practice Doctor of Nursing Practice (DNP) project. KCAMP's objective was to determine whether community-based asthma education, selfmanagement, self-efficacy, an asthma action plan, journal writing, and use of peak flow meters reduce asthma exacerbations. The literature supports these effective interventions for asthma control (Andrews, Jones, & Mullan, 2014; Chen, Sheu, Chang, Wang, & Huang, 2010; Federman et al., 2013). KCAMP was designed with community-based interventions to improve the practice of management of asthma, decrease hospital and doctors' visits' costs, and improve the lives of people who have asthma. Fourteen adult residents with asthma from the Kaʻu District, ages 28 to 75, participated in the program. There were 64% (n = 9) females and 36% (n = 5) males. The racially diverse group included ten Hawaiians, three Asians, and one Caucasian.